Hepato-splenic Microabscesses in Inmunocompetent Patients (Revista de Medicina Clinica, 2024)
Cat scratch disease is a benign infection that classically leads to localized self-limited lymphadenopathy. However, there are disseminated forms that can occur in immunocompromised subjects and, rarely, in immunocompetent subjects. We present the case of a 23-year-old male with no history of interest, who presented with vespertine fever of 2 weeks duration and arthralgia of the right hip. Abdominal magnetic resonance imaging (MRI) showed small hepatic and splenic lesions compatible with microabscesses. Serological studies were carried out which, along with the clinical and radiological alterations, allowed to establish the diagnosis of disseminated Bartonella henselae infection.
Keywords: Bartonella; Cat; Infection; Diagnosis; Treatment